Em prol do respeito linguístico: elaboração de sequência didática sobre "para eu/mim + infinitivo" - Carvalho, Larissa Peres Vitti de (Universidade Federal de São Carlos, 2024)
The main objective of this dissertation was to develop a didactic sequence for high school students, focusing on a specific variable phenomenon: the pronoun eu/mim + infinitive in sentences beginning with the preposition para. The use of para mim + infinitive, often stigmatized by different social groups, was discussed based on a bibliographical survey that reveals the linguistic prejudice associated with it. The proposal included the application of a questionnaire to validate observations and guide the development of the didactic sequence, promoting practices of linguistic respect (Scherre, 2021) in the classroom. This research was based on the assumptions of Variationist Sociolinguistics (Weinreich; Labov; Herzog, 2006 [1968]; Labov, 2008 [1972]), delving deeper into discussions about linguistic variation in the educational context (Bortoni-Ricardo, 2004; Vieira, 2018). To approach the para eu/mim + infinitive, we started from studies by Figueiredo (2007), Novais (2018), Santos and Paim (2018), Gomes (2019), Brandão, Biazolli and Sene (2020) and Vaz (2020). The development of the didactic sequence took into account the ideas of Dolz, Noverraz and Schneuwly (2004) and Vieira (2018). The results obtained from the questionnaire reinforced the stigma attached to the para mim + infinitive variant among the students, as well as highlighting their lack of knowledge regarding concepts such as variation, prejudice, and linguistic respect. Therefore, the didactic sequence developed was designed to address these gaps, with the aim of contributing activities that encourage students to think about language use in a more respectful manner.
For the linguistic respect: preparation of a didatic sequence on "para eu/mim + infinitive"
Keywords: Crenças e atitudes; Preconceito linguístico; Respeito linguístico; Sequência didática; Sociolinguística; Beliefs and attitudes; Linguistic prejudice; Linguistic respect; Didactic sequence; Sociolinguistics; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA